IMPLEMENTASI PROFIL PELAJAR PANCASIL DALAM MEMBANGUN KARAKTER BERGOTONG ROYONG DI KELAS V SD MUHAMMADIYAH 1 NGIMBANG: IMPLEMENTASI PROFIL PELAJAR PANCASIL DALAM MEMBANGUN KARAKTER BERGOTONG ROYONG DI KELAS V SD MUHAMMADIYAH 1 NGIMBANG - Dwi Nur Agustin; Ari Susandi; Humairah Humairah (Universitas Negeri Medan, 2026)
This study aims to determine how the implementation of the Pancasila student profile in building the character of mutual cooperation in fifth-grade students of SD Muhammadiyah 1 Ngimbang Lamongan. This research method is descriptive qualitative research. The research subjects included fifth-grade students and fifth-grade teachers. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman model with triangulation of sources, techniques, and time. Aspects studied in forming the character of mutual cooperation include collaboration, caring, and sharing. The results of the study show that students demonstrate the ability to work together, care for friends and the environment, and are willing to share information and learning tools. The implementation of the values in the Pancasila student profile has been proven to play an important role in building the character of mutual cooperation in students, so it needs to be supported continuously through habituation programs, teacher training, and strengthening a collaborative learning environment.